Local environment of metal ions in phthalocyanines: K-edge X-ray absorption spectra. Issue 34 (11th August 2016) - Rossi, G.; d'Acapito, F.; Amidani, L.; Boscherini, F.; Pedio, M.
Abstract : We describe a model for interpreting XAFS spectra of metal phthalocyanines. The near edge spectra are reproduced in a full potential approach. Abstract : We report a detailed study of the K-edge X-ray absorption spectra of four transition metal phthalocyanines (MPc, M = Fe, Co, Cu and Zn). We identify the important single and multiple scattering contributions to the spectra in the extended energy range and provide a robust treatment of thermal damping; thus, a generally applicable model for the interpretation of X-ray absorption fine structure spectra is proposed. Consistent variations of bond lengths and Debye Waller factors are found as a function of atomic number of the metal ion, indicating a variation of the metal–ligand bond strength which correlates with the spatial arrangement and occupation of molecular orbitals. We also provide an interpretation of the near edge spectral features in the framework of a full potential real space multiple scattering approach and provide a connection to the local electronic structure.